2015
DOI: 10.5041/rmmj.10201
|View full text |Cite
|
Sign up to set email alerts
|

From Research to Reality: Minimizing the Effects of Hospitalization on Older Adults

Abstract: This review examines ways to decrease preventable effects of hospitalization on older adults in acute care medical (non-geriatric) units, with a focus on the Israeli experience at the Rambam Health Care Campus, a large tertiary care hospital in northern Israel. Hospitalization of older adults is often followed by an irreversible decline in functional status affecting their quality of life and well-being after discharge. Functional decline is often related to avoidable effects of in-hospital procedures not caus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
34
0
13

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(47 citation statements)
references
References 91 publications
0
34
0
13
Order By: Relevance
“…However, although informing is perceived as an important intervention, it is not implemented very often, which may compromise the involvement of informal caregivers. According to Admi et al (2015), the involvement of informal caregivers is a key psychosocial risk factor in the health/illness transition process. Furthermore, nurses have consistent perceptions of the interventions observing and managing, and different perceptions of performing, attending, and informing.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, although informing is perceived as an important intervention, it is not implemented very often, which may compromise the involvement of informal caregivers. According to Admi et al (2015), the involvement of informal caregivers is a key psychosocial risk factor in the health/illness transition process. Furthermore, nurses have consistent perceptions of the interventions observing and managing, and different perceptions of performing, attending, and informing.…”
Section: Discussionmentioning
confidence: 99%
“…Osuna-Pozo, Ortiz-Alonso, Vidán, Ferreira, and Serra-Rexach (2013) have reported that older people's main risk factors for FD associated with hospitalization are advanced age, lack of mobility, cognitive changes, and functional status prior to hospitalization. Recent studies conducted with older inpatients in acute care settings (medicine and surgery units) found an increase of FD in ADLs and IADLs when comparing FC before admission, during hospitalization, and after clinical discharge (Cação, 2017 Admi et al, 2015). According to the same authors, the involvement of informal caregivers during hospitalization may be essential.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…At the time, they represented 16.11% of the population and contributed to 27.85% of hospitalizations, and to 36.47% of the resources paid for them (2) . In addition, hospitalized older adults suffer significant reduction in functionality and often receive discharge with inferior capacity compared to the functional condition of admission (3) .…”
Section: Introductionmentioning
confidence: 99%
“…I nsufficient mobility is a significant contributor to hospitalacquired functional decline in older adults (Admi, Shadmi, Baruch, & Zisberg, 2015;Brown, Redden, Flood, & Allman, 2009;Cadogan & D'Ambruoso, 2012). Hospitalacquired functional decline is alarming because escalating rates of hospitalization can be expected in the near future as the number of older adults in the United States is predicted to increase to more than 70 million by 2030 (Administration on Aging, 2012).…”
mentioning
confidence: 99%